2013
DOI: 10.1155/2013/290565
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of p38 Mitogen-Activated Protein Kinases Affects KC/CXCL1-Induced Intraluminal Crawling, Transendothelial Migration, and Chemotaxis of NeutrophilsIn Vivo

Abstract: p38 mitogen-activated protein kinase (MAPK) signalling is critical in the pathophysiology of a variety of inflammatory processes. Leukocyte recruitment to the site of inflammation is a multistep process governed by specific signalling cascades. After adhesion in the lumen, many leukocytes crawl to optimal sites at endothelial junctions and transmigrate to extravascular tissue in a Mac-1-dependent manner. The signalling mechanisms that regulate postadhesion steps of intraluminal crawling, transmigration, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
1
17
1
Order By: Relevance
“…This might be due to 1) CD11b and CD66b being stored in different granules with different threshold for degranulation, 17, 36, 38, 5255 2) our assessments were on neutrophils (both untreated and p38 MAPK-blocked), already adhered to a fibronectin-coated surface, 56–58 or 3) our separation of neutrophils from other blood components. In previous studies that have shown up-regulation of these adhesion molecules, stimulation was frequently applied in the presence of other cell type.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to 1) CD11b and CD66b being stored in different granules with different threshold for degranulation, 17, 36, 38, 5255 2) our assessments were on neutrophils (both untreated and p38 MAPK-blocked), already adhered to a fibronectin-coated surface, 56–58 or 3) our separation of neutrophils from other blood components. In previous studies that have shown up-regulation of these adhesion molecules, stimulation was frequently applied in the presence of other cell type.…”
Section: Resultsmentioning
confidence: 99%
“…The mouse cremaster muscle preparation was used to study dynamic leukocyte-endothelial interactions in microvasculature as described previously (6,7,11,33). For induction of neutrophil recruitment, a piece of agarose gel (∼1 mm 3 ) containing the optimal concentration of murine chemokine CXCL2 (0.5 mmol/l; R&D Systems, Minneapolis, MN) was placed and held on the surface of the cremaster muscle in a preselected area 350 mm from and parallel to the observed postcapillary venule.…”
Section: Intravital Microscopymentioning
confidence: 99%
“…For induction of neutrophil recruitment, a piece of agarose gel (∼1 mm 3 ) containing the optimal concentration of murine chemokine CXCL2 (0.5 mmol/l; R&D Systems, Minneapolis, MN) was placed and held on the surface of the cremaster muscle in a preselected area 350 mm from and parallel to the observed postcapillary venule. Leukocyte rolling velocity (mm/s), leukocyte rolling flux (cells/min), and the number of adherent (cells/100-mm venule) and emigrated neutrophils (cells/235 3 208 mm 2 field) were determined in the cremasteric postcapillary venule (25-40 mm diameter) using video-playback analysis (6,7,11,33). By using ImageJ software (National Institutes of Health) and timelapsed video analysis, neutrophil intraluminal crawling, transmigration time, and extravascular chemotaxis were quantified as described previously (11,33,34).…”
Section: Intravital Microscopymentioning
confidence: 99%
See 2 more Smart Citations